Characterization of in vitro antimicrobial activity of gyrophoric acid isolated from Parmotrema indicum on methicillin-resistant Staphylococcus aureus - Thang Truong Le,, Huy Thuc Duong, Chuong Hoang Nguyen (Journal of Applied Pharmaceutical Science, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) is a group of pathogenic bacteria associated with hard-to-treat infections in humans, which require new, effective antibiotics for treatment. In the search for new candidates for antibiotics against MRSA, we investigated the in vitro antimicrobial activity of gyrophoric acid isolated from the lichen Parmotrema indicum on MRSA. Gyrophoric acid exerted antimicrobial activity mainly on Gram-positive bacteria and one fungal strain, Candida albicans. The minimum inhibitory concentration (MIC) value for MRSA was 32 μg/ml, and at 8 × MIC, gyrophoric acid showed a bactericidal effect on MRSA after 24 hours of culture. This compound showed a low mutation frequency of 2.4 × 10−9 by a single-step resistance test. Gyrophoric acid expressed a synergistic effect with the antibiotic ampicillin that reduced 16-fold the MIC value of ampicillin on MRSA. Gyrophoric acid showed selective toxicity towards MRSA other than human cell lines, with the selective index ranging from 5.43-fold to 8.78-fold. Biofilm formation of MRSA was inhibited by gyrophoric acid starting from the concentration of 2 × MIC, and the biofilm inhibition was 94% at 16 × MIC of gyrophoric acid. The morphology of MRSA under treatment with gyrophoric acid showed a demolition of the cell envelope of the strain revealed by scanning electron microscope. The results of this study proved that gyrophoric acid is a good compound in the “hit validation and declaration” stage of the development procedure of a new antibiotic candidate for MRSA infection treatment.
Keywords: Gyrophoric acid, antimicrobial activity, MRSA, Parmotrema indicum, selective bacterial toxicity